The Impact of Positive Affirmations on the Self-Confidence Levels of Adolescent Girls - Marauleng, Anggi Agata (Acta Psychologia, 2025)
This study explores the relationship between positive affirmations and self-confidence levels in adolescent girls. Adolescence is a critical period for the development of self-esteem and identity, often characterized by fluctuating self-confidence. The purpose of this research was to examine whether engaging in daily positive affirmations could significantly improve self-confidence in adolescent girls. A total of 100 adolescent girls, aged 12 to 18, participated in this study, which was conducted over a four-week period. The participants were divided into an experimental group, which practiced daily positive affirmations, and a control group, which received no intervention. Self-confidence levels were measured using a standardized self-report questionnaire before and after the intervention. The results revealed a significant increase in self-confidence in the experimental group compared to the control group. These findings suggest that positive affirmations can be an effective psychological tool for enhancing self-confidence among adolescent girls. The study also discusses limitations, such as sample size and reliance on self-reported data, and suggests avenues for future research, including longer intervention periods and more diverse samples. The implications of these findings are significant for educational and therapeutic settings, where positive affirmations could be integrated into programs aimed at promoting emotional well-being and resilience in adolescents.